REVIEW: PENDEKATAN LENGTH-BASE SPAWNING POTENSIAL RATIO (LB-SPR) IKAN KURAU (Eleutheronema tetradactylum) DI PERAIRAN PULAU BENGKALIS PROVINSI RIAU - Kholis, Muhammad Natsir (Universitas Muara Bungo, 2023)
Estimating the utilization status of kurau fish resources by other methods using limited data needs to be tried, as a comparison in formulating policies. The aim of this study was to determine the utilization status of kurau fish resources through the Length-Based Spawning Potential Ratio (LB-SPR) approach in the waters of Bengkalis Island. The method used in this study was a review of kurau fish data from July to September 2016. Data were analyzed descriptively using the LB-SPR method. The results showed that the utilization status of kurau fish resources through the LB-SPR approach in the waters of Bengkalis Island was fully moderate (still in moderate condition) with an SPR of 30%, the SL50 value was greater than the Lm value (SL50Lm) so that most of the fish caught had been worth catching. This condition indicates that fishing activities are still in a safe status, but need to be controlled so that the fish caught do not get smaller. The status of the kurau fishery is still relatively good, and can be used massively, but it needs good management to avoid overfishing.